Pile driving noise induces transient gait disruptions in the longfin squid (Doryteuthis pealeii) - Cones, Seth F.; Jézéquel, Youenn; Ferguson, Sophie; Aoki, Nadège; Mooney, T. Aran (Frontiers in Marine Science, 2022)
Anthropogenic noise is now a prominent pollutant increasing in both terrestrial and 33 marine environments. In the ocean, proliferating offshore windfarms, a key renewable energy 34 source, are a prominent noise concern, as their pile driving construction is among the most 35 intense anthropogenic sound sources. Yet, across taxa, there is little information of pile driving 36 noise impacts on organismal fine-scale movement, despite its key link to individual fitness. Here, 37 we experimentally quantified the swimming behavior of an abundant squid species (Doryteuthis 38 pealeii) of vital commercial and ecological importance in response to in situ pile driving activity 39 on multiple temporal and spatial scales (thus exposed to differing received levels, or noise-40 doses). Pile driving induced energetically costly alarm-jetting behaviors in most (69%) 41 individuals at received sound levels (in zero to peak) of 112-123 dB re 1 μm s-2, levels similar to 42 those measured at the kilometer scale from some wind farm construction areas. No responses 43 were found at a comparison site with lower received sound levels. Persistence of swimming 44 pattern changes during noise-induced alarm responses, a key metric addressing energetic effects, 45 lasted up to 14 s and were significantly shorter in duration than similar movement changes 46 caused by natural conspecific interactions. Despite observing dramatic behavioral changes in 47 response to initial pile driving noise, there was no evidence of gait changes over an experiment 48 day. These results demonstrate that pile driving disrupts squid fine-scale movements, but impacts 49 are short-lived suggesting that offshore windfarm construction may minimally impact the 50 energetics of this ecologically key taxon. However, further work is needed to assess potential 51 behavioral and physiological impacts at higher noise levels.